Embryo Manipulation and Imprinting - Marchesi, Dennis E.; Qiao, Jie; Feng, Huai L. (Seminars in Reproductive Medicine, 2012)
As the use of assisted reproductive technologies (ART) continues to rise worldwide, it remains of the upmost importance to maintain the safety of those techniques used in ART. Many of these practices are unique to this discipline; as such, it becomes difficult to assess the true risks that the potential offspring may be subjected to under this type of treatment. Removal of oocytes from a woman's body during an in vitro fertilization (IVF) cycle offers an increased opportunity for routine cellular processes to go awry. Specifically, epigenetic modifications and imprinting diseases are rare among the general population; however, although their incidence among IVF-conceived children is also rare, their frequency in this population remains elevated compared with universal rates. Recent investigations have directly attributed their occurrences to the use of ART and IVF to achieve a successful pregnancy. This review discusses the major cellular manipulations of a typical IVF cycle to assess the potential risks versus the reported risks. These manipulations include preimplantation genetic diagnosis and screening, intracytoplasmic sperm injection, ooplasmic transfer, embryo culture, in vitro maturation, and cryopreservation. Oocyte and embryo handling is a delicate part of the IVF process that continues to improve. The safety of those potential improvements is also discussed.
Keywords: PGD/PGS; ICSI; oocyte/embryo culture; IVF safety; imprinting diseases